Adam Smith and Richard Price on a Free Society of Equals. Issue 2 (13th February 2022) - Whalen, Nicole
Abstract: In this article, I examine two competing republican ideals of a free society of equals in the eighteenth century. I claim that while the value of nondependency was central to the economic outlooks of both Adam Smith and Richard Price, their evaluations of free-market practices were dramatically distinct. In doing so, I introduce a new interpretation of the typologies of republicanism in the eighteenth century.